MEMAHAMI INDONESIA MELALUI PRESPEKTIF NASIONALISME, POLITIK IDENTITAS, SERTA SOLIDARITAS - Mifdal Zusron Alfaqi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: The diversity of ethnic identity politics, race, between groups and religions in Indonesia requires us to live tolerance and have a high sense of national solidarity. Besides the emergence of Indonesian nationalism emerged from the resistance against colonialism also arise because of na-tional solidarity Adaiah Indonesia. but now the Indonesian people experiencing problems on all three. So by learning to understand Indonesia of glasses nationalism, identity politics, and solidarity will grow our national spirit.Keywords: nationalism, identity politics, solidarity